A high-performance cement-based composite material for repair and reinforcement engineering and its preparation method

By improving the glue and fiber system of cement-based composite materials and optimizing the admixture composition, high-ductility concrete with large flow state, fast hardness and high strength is prepared, which solves the problems of low mechanical strength, long hardening time, poor durability and easy cracking in the repair and reinforcement projects of existing materials, achieving efficient and rapid repair and high performance requirements.

CN119774960BActive Publication Date: 2025-06-03CNBM ZHONGYAN TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510287050.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-06-03
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

In the repair and reinforcement projects, existing cement-based building materials have problems such as low mechanical strength, long hardening time, poor durability and easy cracking, which are difficult to meet the requirements of rapid repair and high performance.

Method used

Compound cement, admixture, quartz sand, mixed fibers, reinforcement, nucleating agent and toughening agent are used as the main raw materials. By improving the glue and fiber system and optimizing the composition of the admixture, high-ductile concrete with large flow state, fast hardness and high strength is prepared.

Benefits of technology

It realizes the high ductility, fast hardness and high strength characteristics of cement-based composite materials, can meet the needs of rapid repair and reinforcement projects, and improves the durability and crack resistance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of cement-based building materials, and in particular to a high-performance cement-based composite material for repair and reinforcement engineering and a preparation method thereof. On the one hand, starting from the binder system, the present invention solves the problems of low mechanical strength and slow hardening time of cement-based composites; on the other hand, starting from the fiber system, a method of modifying a variety of fibers is selected to make the fibers more easily dispersed and uniformly dispersed in the mortar, ensuring that the paste has relatively good workability, and optimizing the admixture to prepare a high-ductility concrete with large fluidity, rapid hardening and high strength, so that it can meet the requirements of rail transit and rapid repair and reinforcement engineering of roads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement-based building materials, and particularly to a high-performance cement-based composite material for repair and reinforcement engineering and a preparation method thereof. Background Art

[0002] The development of the economy requires developed transportation for guarantee. Along with the rapid development of the transportation industry, road and track facilities are affected by the increase in service life and traffic volume, and problems such as pavement wear, aging, and damage begin to occur. This not only affects transportation efficiency but may also pose safety hazards.

[0003] Therefore, the repair and reinforcement work becomes particularly important. Currently, ultra-early-strength concrete or polymer-modified concrete is mostly used for the emergency repair of pavements, tracks, and tunnel structures. Although these products can reach high strength within a few hours in the short term to achieve the purpose of quickly restoring traffic, the later strength will partially shrink back, and the durability of the materials is poor, and cracking is likely to occur.

[0004] With the increasing demand for rapid repair and reinforcement in the construction industry, the problems of traditional concrete materials, such as poor durability, weak resistance to deformation loads, and insufficient ductility, can no longer meet the requirements of rapid construction and high performance.

[0005] High-ductility concrete is a fiber-reinforced cement-based composite material with excellent ductility, high damage resistance, high durability, and high strength (compressive and tensile).

[0006] Due to its excellent performance, it has relatively wide applications in the seismic reinforcement of building structures and the repair and reinforcement of old buildings.

[0007] Currently, most of the ECC materials available on the market are designed for building structure reinforcement, but their applications in emergency repair operations are less. Moreover, the dosage of cementitious materials such as fly ash and silica fume in the materials accounts for a relatively high proportion, resulting in slow strength growth, low later strength, high viscosity of the concrete, poor workability, and being not conducive to construction. Therefore, it is particularly important to develop a high-ductility concrete material with early strength, rapid hardening, and high fluidity. Summary of the Invention

[0008] To solve the problems existing in the prior art, the present invention provides a high-performance cement-based composite material for repair and strengthening projects, which is also a high-ductility concrete and is also called high-ductility cement-based material. Specifically, the present invention uses compound cement, admixture, quartz sand, hybrid fiber, strengthening agent, nucleating agent, toughening agent as the main raw materials. On the one hand, starting from the binder system, it solves the problems of low mechanical strength and slow hardening time of cement-based composites. On the other hand, starting from the fiber system, it selects the method of modifying a variety of fibers to make the fibers more easily dispersed and evenly dispersed in the mortar, ensuring that the paste has relatively good workability, and optimizing the admixture to prepare a high-ductility concrete with high fluidity, rapid hardening and high strength, so as to meet the needs of rapid repair and strengthening projects.

[0009] Specifically, the high-performance cement-based composite material for repair and strengthening projects of the present invention is composed of the following raw materials in parts by weight: 100-120 parts of compound cement, 30-60 parts of admixture, 90-120 parts of quartz sand, 1-3 parts of hybrid fiber, 2-5 parts of strengthening agent, 1-3 parts of nucleating agent, 1-2 parts of toughening agent, and 38-42 parts of water.

[0010] Preferably, the compound cement is composed of Portland cement, sulfoaluminate cement, and aluminate cement mixed in a mass ratio of (2-4):(1-4):(1-2). The present invention uses three kinds of cements for compounding to shorten the setting time, improve the early strength, and ensure the later strength of the high-ductility concrete.

[0011] Preferably, the admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of (10-30):(8-12):(5-7).

[0012] Preferably, the hybrid fiber is composed of ozone-modified PE fiber and PVA fiber mixed in a mass ratio of 1:(0.9-1.2). The present invention modifies the PE fiber by ozone modification to enable more hydrophilic groups such as hydroxyl and carboxyl groups to adhere to the fiber surface, improving the hydrophilicity, thereby promoting the fluidity of the high-ductility concrete; selecting ozone-modified PE fiber and PVA fiber for compound admixture in a certain proportion to produce a good hybrid effect and improve the toughness and crack resistance of the concrete.

[0013] Preferably, the strengthening agent is composed of water reducing agent, defoaming agent, redispersible latex powder, and early strength agent mixed in a mass ratio of (2-4):(1-4):(1-4):(1-2).

[0014] Preferably, the nucleating agent is composed of nano-SiO 2 、nano-CaCO 3 、nano-graphene oxide mixed in a mass ratio of (2-5):(1-3):(3-5). The present invention uses nano-SiO 2, nano-CaCO 3 As an inorganic nucleating agent, when compounded with a nano-graphene oxide organic nucleating agent, it innovatively integrates nanotechnology to provide cement nucleation sites, enabling the compound cement to achieve early strength effects in the early stage.

[0015] Preferably, the toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansive agent, calcareous raw material, and dispersant in a mass ratio of (30 - 40):(55 - 75):(10 - 22):(3 - 15):(1 - 2.5). The addition of the toughening agent in the present invention can optimize the composition of the cementitious material, regulate the mineral phase composition of the cement, change the hydration reaction process of different mineral phases in the cement, and affect the formation rate of ettringite. Moreover, a large number of self-generated large-sized ettringite whiskers are formed during the reaction of the toughening agent. The length of the whiskers can reach 20 - 50 μm, which is 2 - 5 times the length of the ettringite formed by the hydration of ordinary cement. The large-sized ettringite whiskers can act as micro-scale fibers, not only capable of playing a "bridging" role to connect various hydration products, but also capable of filling the pore-like structure in the cement to make the structure denser, thereby achieving an in-situ self-toughening effect. In addition, it can achieve a multi-scale fiber synergistic strengthening effect with the hybrid fibers of the present invention, solve the problem of uneven dispersion of fibers in the cement, and effectively improve the continuity of high-ductility concrete materials, realizing strengthening and toughening.

[0016] Preferably, the strength grade of each cement in the compound cement is ≥42.5.

[0017] Preferably, the preparation process of the ozone-modified PE fiber is as follows: Wash and dry the PE fiber, put it into an ozone generator for oxidation treatment, and then wash and dry it again to obtain the product.

[0018] Preferably, the oxidation treatment temperature is 60 - 80°C, the ozone gas flux is 200 - 500 mL / min, the ozone concentration is set at 19 - 22 g / L, and the oxidation treatment time is 25 - 40 min.

[0019] Preferably, the length of the PE fiber is 6 - 18 mm.

[0020] Preferably, the water reducer is a polycarboxylate water reducer, the defoaming agent is an organosilicon defoaming agent, and the early strength agent is at least one of tartaric acid, lithium carbonate, and sodium nitrite.

[0021] Preferably, the gypsum is at least one of anhydrite, gypsum dihydrate, and hemihydrate gypsum, the calcareous raw material is at least one of calcium oxide, quicklime, and slaked lime, and the dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate.

[0022] Preferably, the chemical composition of the toughening agent includes: CaO 40 - 58%, SiO 2 9 - 15%, Al 2 O 34 - 27%, SO 3 4 - 11%, Fe 2 O 3 2.5 - 8.5%.

[0023] Preferably, the specific surface area of the toughening agent is 400 - 600 m 2 / kg.

[0024] The present invention also relates to a preparation method of the high - performance cement - based composite material for the above - mentioned repair and strengthening project. Specifically, it includes the following steps:

[0025] 1) Weigh each raw material according to parts by weight,

[0026] 2) Mix the compound cement, admixture, quartz sand, strengthening agent, and toughening agent evenly to obtain dry materials,

[0027] 3) Mix the nucleating agent and water evenly to obtain liquid materials,

[0028] 4) Slowly add the liquid materials and hybrid fibers to the dry materials and mix evenly to obtain slurries,

[0029] 5) Mold and cure the slurries to obtain the product.

[0030] Preferably, the curing in step 5) adopts standard curing. Specific Embodiments

[0031] To characterize the technical effects of the present invention, a cement - based repair material was prepared and its performance was tested. During the test, the strength of each cement in the compound cement was 42.5 grade, the water - reducing agent was a polycarboxylate water - reducing agent, the defoaming agent was an organosilicon defoaming agent, and the preparation process of the ozone - modified PE fiber was as follows: The PE fiber was cleaned, dried, put into an ozone generator for oxidation treatment. The oxidation treatment temperature was 70 °C, the ozone gas flux was 400 mL / min, the ozone concentration was set at 20 g / L, and the oxidation treatment time was 30 min. Then it was cleaned and dried again to obtain the product.

[0032] Example 1

[0033] The cement - based repair material consists of the following raw materials by weight: 110 parts of compound cement, 60 parts of admixture, 100 parts of quartz sand, 2 parts of hybrid fibers, 3 parts of strengthening agent, 2 parts of nucleating agent, 1.5 parts of toughening agent, and 40 parts of water,

[0034] The compound cement is composed of Portland cement, sulphoaluminate cement, and aluminate cement mixed in a mass ratio of 2:3:1,

[0035] The admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of 25:8:6,

[0036] The hybrid fiber is composed of ozone-modified PE fiber and PVA fiber mixed in a mass ratio of 1:1.

[0037] The reinforcing agent is composed of water reducer, defoamer, redispersible latex powder, and lithium carbonate mixed in a mass ratio of 2:3:4:2.

[0038] The nucleating agent consists of nano-SiO 2 , nano-CaCO 3 , and nano-graphene oxide mixed in a mass ratio of 5:2:4.

[0039] The toughening agent is obtained by grinding a mixture of calcium aluminate clinker, gypsum, CSA expansive agent, quicklime, and sodium tripolyphosphate in a mass ratio of 32:70:15:7:1.2.

[0040] After testing, the initial fluidity of the slurry is 240 mm, the flexural strength at 2 h is 7.7 MPa, the flexural strength at 60 d is 29.6 MPa, the compressive strength at 2 h is 22.3 MPa, the compressive strength at 60 d is 94.9 MPa, the equivalent flexural strength at 60 d is 20.6 N / mm 2 , and the equivalent flexural toughness at 60 d is 361.4 kJ / m 3 .

[0041] Example 2

[0042] The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water.

[0043] The compound cement is composed of Portland cement, sulphoaluminate cement, and aluminate cement mixed in a mass ratio of 3:3:2.

[0044] The admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of 30:10:5.

[0045] The hybrid fiber is composed of ozone-modified PE fiber and PVA fiber mixed in a mass ratio of 1:0.9.

[0046] The reinforcing agent is composed of water reducer, defoamer, redispersible latex powder, and sodium nitrite mixed in a mass ratio of 4:1:2:1.

[0047] The nucleating agent consists of nano-SiO 2 , nano-CaCO 3 , and nano-graphene oxide mixed in a mass ratio of 3:1:4.

[0048] The toughening agent is obtained by grinding a mixture of calcium aluminate clinker, gypsum, CSA expansive agent, calcium oxide, and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0049] After testing, the initial fluidity of the slurry is 230 mm, the flexural strength at 2 h is 8.0 MPa, the flexural strength at 60 d is 30.8 MPa, the compressive strength at 2 h is 21.6 MPa, the compressive strength at 60 d is 90.1 MPa, and the equivalent flexural strength at 60 d is 21.8 N / mm 2 , and the equivalent flexural toughness at 60 d is 433.7 kJ / m 3 .

[0050] Comparative Example 1

[0051] The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of strengthening agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water.

[0052] The compound cement is composed of ordinary Portland cement and sulphoaluminate cement mixed in a mass ratio of 1:1.

[0053] The admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of 30:10:5.

[0054] The hybrid fiber is composed of ozone-modified PE fiber and PVA fiber mixed in a mass ratio of 1:0.9.

[0055] The strengthening agent is composed of water reducer, defoamer, redispersible latex powder, and sodium nitrite mixed in a mass ratio of 4:1:2:1.

[0056] The nucleating agent is composed of nano-SiO 2 , nano-CaCO 3 , and nano-graphene oxide mixed in a mass ratio of 3:1:4.

[0057] The toughening agent is ground from calcium aluminate clinker, gypsum, CSA expansion agent, calcium oxide, and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0058] After testing, the initial fluidity of the slurry is 250 mm, the flexural strength at 2 h is 6.5 MPa, the flexural strength at 60 d is 24.9 MPa, the compressive strength at 2 h is 13.8 MPa, the compressive strength at 60 d is 80.5 MPa, and the equivalent flexural strength at 60 d is 15.7 N / mm 2 , and the equivalent flexural toughness at 60 d is 283.4 kJ / m 3 .

[0059] Comparative Example 2

[0060] The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of strengthening agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water.

[0061] The compound cement is formed by mixing Portland cement, sulfoaluminate cement, and aluminate cement in a mass ratio of 3:3:2.

[0062] The admixture is formed by mixing fly ash, slag powder, and silica fume in a mass ratio of 30:10:5.

[0063] The hybrid fiber is formed by mixing PE fiber and PVA fiber in a mass ratio of 1:0.9.

[0064] The enhancer is formed by mixing water reducer, defoamer, redispersible latex powder, and sodium nitrite in a mass ratio of 4:1:2:1.

[0065] The nucleating agent consists of nano-SiO 2 , nano-CaCO 3 , and nano-graphene oxide in a mass ratio of 3:1:4.

[0066] The toughening agent is ground from calcium aluminate clinker, gypsum, CSA expansive agent, calcium oxide, and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0067] After testing, the initial fluidity of the slurry is 190 mm, the flexural strength at 2 h is 4.6 MPa, the flexural strength at 60 d is 23.2 MPa, the compressive strength at 2 h is 15.1 MPa, the compressive strength at 60 d is 73.6 MPa, the equivalent flexural strength at 60 d is 10.5 N / mm 2 , and the equivalent flexural toughness at 60 d is 256.4 kJ / m 3 .

[0068] Comparative Example 3

[0069] The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of enhancer, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water.

[0070] The compound cement is formed by mixing Portland cement, sulfoaluminate cement, and aluminate cement in a mass ratio of 3:3:2.

[0071] The admixture is formed by mixing fly ash, slag powder, and silica fume in a mass ratio of 30:10:5.

[0072] The hybrid fiber is formed by mixing ozone-modified PE fiber and PVA fiber in a mass ratio of 1:0.9.

[0073] The enhancer is formed by mixing water reducer, defoamer, redispersible latex powder, and sodium nitrite in a mass ratio of 4:1:2:1.

[0074] The nucleating agent consists of nano-CaCO 3, and graphene oxide nanosheets are mixed in a mass ratio of 1:1.

[0075] The toughening agent is prepared by grinding a mixture of calcium aluminate clinker, gypsum, CSA expansive agent, calcium oxide, and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0076] After testing, the initial fluidity of the slurry is 210 mm, the flexural strength at 2 h is 5.4 MPa, the flexural strength at 60 d is 22.7 MPa, the compressive strength at 2 h is 10.6 MPa, the compressive strength at 60 d is 73.0 MPa, and the equivalent flexural strength at 60 d is 12.4 N / mm 2 , and the equivalent flexural toughness at 60 d is 219.7 kJ / m 3 .

[0077] Comparative Example 4

[0078] The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water.

[0079] The compound cement is composed of Portland cement, sulphoaluminate cement, and aluminate cement mixed in a mass ratio of 3:3:2.

[0080] The admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of 30:10:5.

[0081] The hybrid fiber is composed of ozone-modified PE fiber and PVA fiber mixed in a mass ratio of 1:0.9.

[0082] The reinforcing agent is composed of water reducer, defoamer, redispersible latex powder, and sodium nitrite mixed in a mass ratio of 4:1:2:1.

[0083] The nucleating agent consists of nano-SiO 2 , nano-CaCO 3 , and graphene oxide nanosheets mixed in a mass ratio of 3:1:4.

[0084] The toughening agent is prepared by grinding a mixture of calcium aluminate clinker, gypsum, and sodium hexametaphosphate in a mass ratio of 54:70:3.

[0085] After testing, the initial fluidity of the slurry is 235 mm, the flexural strength at 2 h is 4.3 MPa, the flexural strength at 60 d is 23.2 MPa, the compressive strength at 2 h is 10.5 MPa, the compressive strength at 60 d is 62.4 MPa, and the equivalent flexural strength at 60 d is 12.7 N / mm 2 , and the equivalent flexural toughness at 60 d is 185.1 kJ / m 3 .

[0086] Comparative Example 5

[0087] Cement-based repair material, which is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of hybrid fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, and 40 parts of water.

[0088] The compound cement is composed of portland cement, sulfoaluminate cement, and aluminate cement mixed in a mass ratio of 3:3:2.

[0089] The admixture is composed of fly ash, slag powder, and silica fume mixed in a mass ratio of 30:10:5.

[0090] The hybrid fiber is composed of PP fiber and PVA fiber mixed in a mass ratio of 1:0.9.

[0091] The reinforcing agent is composed of water reducer, defoamer, redispersible latex powder, and sodium nitrite mixed in a mass ratio of 4:1:2:1.

[0092] The nucleating agent is composed of nano-SiO 2 , nano-CaCO 3 , and nano-graphene oxide mixed in a mass ratio of 3:1:4.

[0093] After testing, the initial fluidity of the slurry is 180 mm, the flexural strength at 2 h is 1.6 MPa, the flexural strength at 60 d is 19.7 MPa, the compressive strength at 2 h is 3.1 MPa, the compressive strength at 60 d is 60.6 MPa, the equivalent flexural strength at 60 d is 4.6 N / mm 2 , and the equivalent flexural toughness at 60 d is 120.3 kJ / m 3 .

[0094] It can be seen from the technical effects of the examples that the cement-based composite material of the present invention has the effect of high-ductility concrete, and has the characteristics of good fluidity, fast hardening and high strength, and can be used for repair and reinforcement projects.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high ductility cement-based material, characterized in that: The invention is composed of the following raw materials in parts by weight: 100-120 parts of compound cement, 30-60 parts of admixture, 90-120 parts of quartz sand, 1-3 parts of mixed fiber, 2-5 parts of reinforcing agent, 1-3 parts of nucleating agent, 1-2 parts of toughening agent, and 38-42 parts of water. The composite cement is prepared by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of (2-4):(1-4):(1-2). The admixture is prepared by mixing fly ash, mineral powder and silica fume in a mass ratio of (10-30):(8-12):(5-7). The hybrid fiber is formed by mixing ozone-modified PE fiber and PVA fiber in a mass ratio of 1:(0.9-1.2). The reinforcing agent is prepared by mixing a water reducing agent, a defoaming agent, a redispersible latex powder and an early strength agent in a mass ratio of (2-4):(1-4):(1-4):(1-2). The nucleating agent is prepared by mixing nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of (2-5):(1-3):(3-5). The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium raw material and dispersant in a mass ratio of (30-40):(55-75):(10-22):(3-15):(1-2.5), and the calcium raw material is at least one of calcium oxide, quicklime and slaked lime.

2. The high ductility cement-based material according to claim 1, characterized in that: The strength grade of each cement in the composite cement is ≥42.

5.

3. The high ductility cement-based material according to claim 1, characterized in that: The ozone-modified PE fiber preparation process comprises: washing and drying the PE fiber, placing the PE fiber in an ozone generator for oxidation treatment, and washing and drying the fiber again to obtain the ozone-modified PE fiber.

4. The high ductility cement-based material according to claim 3, characterized in that: The oxidation treatment temperature is 60-80° C., the ozone gas flux is 200-500 mL / min, the ozone concentration is set at 19-22 g / L, and the oxidation treatment time is 25-40 min.

5. The high ductility cement-based material according to claim 3, characterized in that: The PE fiber length is 6-18 mm.

6. The high ductility cement-based material according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, the defoamer is an organosilicon defoamer, and the early strength agent is at least one of tartaric acid, lithium carbonate, and sodium nitrite.

7. The high ductility cement-based material according to claim 1, characterized in that: The gypsum is at least one of anhydrite, dihydrate gypsum and hemihydrate gypsum, and the dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate.

8. The high ductility cement-based material according to claim 1, characterized in that: The chemical composition of the toughening agent includes: CaO 40-58%, SiO 2 9-15%, Al 2 O 3 4-27%, SO 3 4-11%, and Fe 2 O 3 2.5-8.5%.

9. The high ductility cement-based material according to claim 1, characterized in that: The specific surface area of ​​the toughening agent is 400-600m 2 / kg.

10. The method for preparing a high ductility cement-based material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Mix the compound cement, admixture, quartz sand, reinforcing agent and toughening agent evenly to obtain dry material. 3) Mix the nucleating agent and water evenly to obtain liquid material. 4) Slowly add the liquid material and mixed fibers into the dry material and mix evenly to obtain slurry. 5) Shape and cure the slurry.

Citation Information

Patent Citations

  • Self-growing nano ettringite fiber toughened concrete and preparation method thereof

    CN115872707A

  • Self-repairing steam-cured concrete material and preparation method thereof

    CN118206352A

  • Polyolefin-based fiber for reinforcing cement and method for producing the same

    JP2003089559A